Grey networks: The contradictory dimensions of Australia's immigration detention system. (15th March 2018) - Neil, David; Peterie, Michelle
Abstract : The notion of dark networks has recently received attention in the literature on policy network analysis. Dark networks are defined as illegal and covert, in contrast to bright networks which are legal and overt. In this article, we suggest a third category – grey networks – which are characterised by their use of secrecy and concealment despite their ostensibly legal status. These networks are subject to contradictory imperatives. They employ methods that cannot be openly acknowledged within the larger legal and social framework in which they function. In this article, we illustrate this concept through an interview‐based study of Australia's immigration detention network. This network enacts a deterrence policy which has been widely condemned as breaching Australia's obligations under international law. At the same time, it is required to maintain a façade of lawfulness and respect for human rights.